Continuity of Care During COVID-19 Lockdown: A Survey on Stakeholders' Experience With Telerehabilitation - Assenza, Carla; Catania, Hilenia; Antenore, Clementina; Gobbetti, Tiziana; Gentili, Paola; Paolucci, Stefano; Morelli, Daniela (Frontiers in Neurology, 2021)
Objective: To explore professionals', adult patients', and children's caregivers' perception and satisfaction with telerehabilitation during COVID-19 lockdown. Design: An observational transversal study on a web-based survey was conducted in order to explore participants' perception and satisfaction of telerehabilitation during COVID-19 lockdown. Setting: The study was conducted at our Outpatient Neurorehabilitation Service. Subjects: All rehabilitation professionals, adult patients, and children's caregivers who accepted telerehabilitation were recruited. Interventions: Participants had to respond to the Client Satisfaction Questionnaire-8 and to a purpose-built questionnaire on their perception and satisfaction of the service provided. Main Measures: Data were analyzed by qualitative statistics and logistic regression models. Results: All 144 caregivers, 25 adult patients, and 50 professionals reported a medium-high level of perception and a high level of satisfaction. Results showed a correlation among caregivers of children aged 0–3 and feeling overwhelmed with remote care (OR = 3.27), a low perception of telerehabilitation for enhancing goals (OR = 6.51), and a high perception of feeling helped in organizing daily activity (OR = 2.96). For caregivers of children aged over 6 years, changes in the therapy plan were related to a low perception of feeling in line with the in-person therapy (OR = 2.61 and OR = 9.61) and a low satisfaction (OR = 5.54 and OR = 4.97). Changes in therapy were related to concern (OR = 4.20). Caregivers under 40 and professionals showed a high probability to perceive telerehabilitation as supportive (OR = 2.27 and OR = 5.68). Level of experience with remote media was shown to influence perception and satisfaction. Interpretation: Telerehabilitation can be a useful practice both during a health emergency and in addition to in-presence therapy.